Pengetahuan Gizi Ibu dan Praktik Diversifikasi Makanan Keluarga di Kelurahan Purworejo, Kecamatan Margoyoso, Pati - Loviana Mufida; Agus Sartono; Mufnaetty Mufnaetty (Jurnal Gizi, 2020)
In daily observations the pattern of food consumption in the Purworejo village community is not so diverse, there are still mothers who are not posyandu participants so that knowledge related to food diversification is lacking while family income levels are quite varied.The purpose of this study was to determine the relationship between maternal nutritional knowledge, level of family food diversity in Purworejo Village, Margoyoso Pati District.His study is a quantitative analytic study with a cross sectional approach. The sample  of this study was housewives in Purworejo Village, Margoyoso Pati District. The number of samples is 88 households which are determined by systematic random sampling. The variables in this study were measured by interviews and questionnaires. The statistical test used in the variables of nutritional knowledge and family income level is Rank Spearman correlation,while the maternal match variable in the posyandu uses Mann Whitney.Found 45.5% of respondents had good nutrition knowledge and 48.9% had poornutrition knowledge. There were 69.3% of respondents did not become Posyandu participants, 52.3% of respondents had poor food diversification. There is a relationship between maternal nutrition knowledge with food diversification practices and there is no difference in Family Food Diversification Practices based on maternal participation in Posyandu.Keywords: nutritional knowledge, Food diversification.